Wage Bargaining and Profitability: A Disaggregative Analysis. - Beckerman, W; Jenkinson, T (1990)
Abstract. Previous analyses of the wage/profit relationship at a disaggregative level in Britain have given positive results for pre-war years but negative results for early post-war years. However, this is probably due to the increasingly unreliable nature of the enterprise- based profits series published in the National Accounts until 1982. We have constructed, instead, what are essentially establishment-based Census data on profits for fourteen manufacturing industries, up to 1986. We have also been able to extend the disaggregative unemployment data, the publication of which also ceased in 1982. The wage equations that we have estimated include profits and unemployment (and other variables) in an explicit Nash bargaining model, in line with widely held views as to the way that wage negotiations are actually conducted. The results obtained show a highly significant role for profits, as well as having other implications, notably the positive (hysteresis) effect of industry unemployment, by contrast with the normal negative effect of aggregate unemployment, and the important effects of relative wages - which play a large role in various disaggregative studies of the propagation of inflation.